2005
DOI: 10.1111/j.0742-2822.2005.04005.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Aortic Transection

Abstract: We report three cases of patients with blunt thoracic trauma, who underwent transesophageal echocardiography (TEE) because of high index of clinical suspicion for acute traumatic aortic syndrome. TEE revealed three different locations of aortic injury one of which was not diagnosed with aortography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…There is a range of reported locations of thoracic aortic injuries in deceleration‐type motor vehicle crashes. Aortic transection occurs at the isthmus in 90% of cases with asc‐ao involvement in only 20% of cases . In other thoracic aortic injury series associated with blunt trauma and deceleration injuries, transection localized to the asc‐ao has even lower reported rates, ranging from 0% in a series of 116 patients to 16% in 272 patients …”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…There is a range of reported locations of thoracic aortic injuries in deceleration‐type motor vehicle crashes. Aortic transection occurs at the isthmus in 90% of cases with asc‐ao involvement in only 20% of cases . In other thoracic aortic injury series associated with blunt trauma and deceleration injuries, transection localized to the asc‐ao has even lower reported rates, ranging from 0% in a series of 116 patients to 16% in 272 patients …”
Section: Discussionsupporting
confidence: 80%
“…Zissimopoulos et al reported three cases of traumatic aortic transection due to a deceleration injury—all diagnosed with TEE. The first patient had a dissection flap beginning at the aortic isthmus extending into the descending aorta, the second had a localized injury in the distal aortic arch (who also had a false negative aortogram performed), and the third case's examination revealed a localized mobile dissection flap just distal to the aortic isthmus.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations